Review of Epilepsy Perceptions and Attitudes Across African Countries - Willie, Michael (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This review synthesizes research on perceptions and misconceptions about epilepsy across various countries, exploring beliefs that attribute epilepsy to supernatural causes, contagion, or mental retardation. It hypothesizes that these misconceptions contribute to the stigmatization and social exclusion of individuals with epilepsy (PwE). Research Design and Methodology: The review compiles findings from studies conducted in Mali, Nigeria, Pakistan, Saudi Arabia, Egypt, and Ethiopia. These studies focus on teachers, parents, and community members and employ qualitative methods such as surveys and interviews. Sampling methodologies vary but include educational and community-based settings. Findings and Discussion: The findings indicate that epilepsy-related misconceptions are widespread, leading to stigma and exclusion from education, employment, and social interactions. Many communities view epilepsy as contagious or caused by supernatural forces, reinforcing discrimination. Teachers and parents play a role in perpetuating these beliefs, further marginalizing PwE. Implications: Addressing epilepsy-related stigma requires targeted education and awareness programs. Healthcare professionals, educators, and community leaders must challenge misconceptions and promote inclusive environments. The review highlights the need for culturally sensitive interventions and further research on effective stigma-reduction strategies.